PENGARUH PENGGUNAAN SEMEN SEBAGAI BAHAN STABILISASI TANAH LEMPUNG LUNAK DI DAERAH GROBOGAN PURWODADI - Hariyanto Hariyanto; Suluh Jatmiko (Universitas PGRI Semarang, 2021)
Geographically Indonesia is located in the tropics, with conditions like this in the rainy season there will be high rainfall and in the dry season there will be hot weather. Weather changes result in repeated cycles of wetting and drying, so that the soil will experience changes in soil volume due to changes in water content. In such problems, special treatment of subgrade which has soft properties is needed. In this case the researcher will use cement as a soil stabilization material in the Grobogan, Purwodadi. The results obtained from the research: classification of Active clays (Montmorilonite), because the soil activity is more than 1, namely> 2.35%. From variations of mixing 0%, 17%, and 23% produce water content (w) of 21.820%, density (Gs) of 2.128%, dry weight (Î³d) of 1.43% shrinkage limit (SL) of 10.56%. Atterberg Limits limit with liquid limit value (LL) of 77.30% and plastic limit (PL) of 60.00%, plasticity index (PI) value of 17.30%. The relationship between OMC and MDD of native soil was obtained by maximum dry weight of 1.432 gr / cm3 at optimum water content of 10.320%. From the results of 17% soil + cement testing the optimum water content value was 8% and the maximum dry weight was 1.65 gr / cm3. From the results of 23% cement + soil testing, the optimum water content was 13% and the maximum dry weight was 1.6 gr / cm3.